Short-Circuit Analysis of DER-Based Microgrids in Connected and Islanded Modes of Operation - Nikola Simic; Luka Strezoski; Boris Dumnic (Energies, 2021)
Since microgrids should be able to smoothly operate in two distinct modes—grid-connected and islanded, their fault currents can widely fluctuate depending on the operational mode. When the microgrid is connected to the grid, the highest fault current, by far, is supplied by the utility grid. In this mode, the fault current contribution from distributed energy resources (DERs) is less than 20%. However, when the microgrid switches to the islanded mode, the fault current contribution from the utility grid is lost and DERs are the sole fault current sources. Thus, the overall fault current in the islanded mode is multiple times lower when compared to the grid connected mode. Moreover, most of the DERs are inverter-based, with limited fault currents, which further reduces the overall fault current in the islanded mode. With the rapid rise of the microgrid penetration around the globe, this phenomenon can adversely influence the relay protection, and thus the microgrid fault current needs to be precisely analyzed. Therefore, the main purpose of this paper is to thoroughly analyze the fault current differences in two distinct operation modes of a microgrid, and to consequently derive conclusions regarding the required improvements in fault calculations and relay protection analysis in emerging microgrids. A representative microgrid test bed is developed and modelled using the in-house developed software as well as in a state-of-the-art hardware-in-the-loop environment. Several different short-circuit faults were simulated and analyzed in both grid-connected and islanded modes. The results show that the fault currents significantly differ depending on the operating mode, and thus highly influence the protection system. Moreover, test results show that the fault calculation algorithms aimed at radial distribution grids, mostly used for microgrid fault calculations in the available literature, need to be further improved to provide precise and time-efficient results when the emerging microgrids are considered. These results provide a valuable insight into the current state of the microgrids’ fault calculation and protection and reveal several important directions for future research.